Progress in Public Expenditure Management in Africa : Evidence from World Bank Surveys - Mohan, Prasad C. (World Bank, Washington, DC, 2012)
One of the World Bank's key advisory roles is to assist its partner countries to make strategic decisions about the use of their public funds. Governments and the Bank together assess the public sector's potential role as a provider, financier, or regulator of services, or simply as a catalyst for private sector activity. The Bank's traditional vehicle for contributing to this kind of analytical work is the Public Expenditure Review (PER). The Africa Region undertook a survey of 20 task managers of PERs in 1997/98. This Note summarizes the main survey findings and key recommendations.